STUDENTS’ NEED ANALYSIS ON SPEAKING MATERIAL: A SURVEY STUDY AT SMA 1 MUHAMMADIYAH BENGKULU - Hayadi, Algrin; Syafryadin, Syafryadin; Kristiawan, Muhammad; Badeni, Badeni (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2025)
This study aims to examine the needs and obstacles faced by students about speaking materials, as proficient speaking skills are crucial for efficient communication. The research seeks to identify the domains in which students encounter challenges in speaking and to gather information regarding their preferences for speaking resources. This study included 30 students in the 11th grade of SMA 1 Muhammadiyah Bengkulu. Interviews were conducted to obtain additional information, in addition to a questionnaire that contained 29 items. Simultaneously, six students conducted interviews at random. According to the questionnaires and interviews of students, the majority of students concur that the most difficult aspect of learning English speaking and fluency is grammar (63.3%) and fluency (13.3%). Additionally, certain students in the interview are unable to identify the exposition text due to its perceived difficulty in conclusion. The interview involved six students who utilized a voice note to document their responses regarding the necessity of speaking materials. The majority of students concurred that they desired to engage in discussions, perform games, and engage in conversation in order to create a friendly and enjoyable learning environment in English. This research provides educators and material developers with valuable insights to address the requirements and challenges of students in speaking materials, thereby enhancing their speaking abilities.